(Invited) Recent Advances in the Modeling of Strain Relaxation and Dislocation Dynamics in ZnSSe/GaAs (001) Heterostructures. (24th April 2020) - Ayers, John E; Kujofsa, Tedi; Raphael, Johanna; Islam, Md Tanvirul; Wales, James; Lindstrom, Kevin; Song, Yifei
Abstract : In this paper we describe state-of-the-art approaches to the modeling of strain relaxation and dislocation dynamics in ZnSSe/GaAs (001) heterostructures. These are based on the extension of the Dodson and Tsao plastic flow model [B. W. Dodson and J. Y. Tsao, Appl. Phys. Lett., 51, 1325 (1987); Appl. Phys. Lett., 52, 852 (1988)] to include compositional grading and multilayers, dislocation interactions, and differential thermal expansion. Important recent breakthroughs have greatly enhanced the capability of the modeling approach in three respects: i) pinning interactions have been included in graded and multilayered structures for the first time, providing a better description of the limiting strain relaxation as well as the dislocation sidewall gettering; ii) a refined model for dislocation-dislocation interactions including jogging provides a more accurate physical description of compositionally-graded layers and step-graded layers; and iii) inclusion of back-and-forth weaving of dislocations provides a better description of dislocation dynamics in structures containing strain reversals, such as strained-layer superlattices and overshoot graded layers. Here we describe these three key advances and illustrate applications of each to practical heterostructures.